2020
DOI: 10.1088/2040-8986/ab877d
|View full text |Cite
|
Sign up to set email alerts
|

Diffraction of bessel beams on 2D amplitude gratings—a new branch in the talbot effect study

Abstract: In this paper, an analytical theory for the diffraction of a Bessel beam of arbitrary order J l (κr) on a 2D amplitude grating is presented. The diffraction pattern in the main and fractional Talbot planes under certain conditions is a lattice of annular microbeams, the diameters of which depend on the grating period, the illuminating beam diameter, the number of the Talbot plane, and the topological charge l. For the rings near the optical axis, the latter reproduces l of the illuminating beam. Experiments ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…This effect is well‐known as the Talbot effect [ 26 ] ; it has been shown that this effect is retained for OVs in the visible [ 24 ] and terahertz ranges. [ 21,23 ] It means that the Talbot effect can be used to create the 3D OVLs by illuminating a 2D amplitude diffraction grating with an OV as shown in Figure 1 a. The 3D intensity distribution can be calculated using the approach proposed in ref.…”
Section: Basic Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This effect is well‐known as the Talbot effect [ 26 ] ; it has been shown that this effect is retained for OVs in the visible [ 24 ] and terahertz ranges. [ 21,23 ] It means that the Talbot effect can be used to create the 3D OVLs by illuminating a 2D amplitude diffraction grating with an OV as shown in Figure 1 a. The 3D intensity distribution can be calculated using the approach proposed in ref.…”
Section: Basic Theorymentioning
confidence: 99%
“…[22] it was proposed a method for producing a close‐packed 2D OV lattice with a controllable structure in the far‐field. So far, the investigations of the OV arrays have been limited to the cross sections of the 3D spatial distributions, [ 21,23 ] except for the 3D reconstruction of a unit cell, [ 18,24 ] although 3D optical lattices without TCs have been intensively studied. [ 9,25 ] A spatial array of the OVs regular in the three dimensions (a 3D lattice) is of particular interest, since it offers unique possibilities for light‐matter interactions, which cannot be obtained using optical lattices without TCs.…”
Section: Introductionmentioning
confidence: 99%
“…Используя метод формирования двух близко расположенных закрученных кольцевых пучков с разнонаправленной радиальной поляризацией [26,27], можно возбуждать плазмоны на торце тонкостенного полого цилиндра [28]. Продемонстрированный в [29]…”
Section: Introductionunclassified
“…The physics behind this phenomenon is interference of diffracted waves, which results in the intensity distribution (image) self-reproduction at distances multiple of Talbot length Z T = 2� 2 / , where is the grating period, is the wavelength of the incident wave. This phenomenon is well-studied, both theoretically and experimentally, for plane waves 33 and theoretically investigated for the beams comprising phase singularities 20,34,35 . In the experiment, the Talbot effect of the OAM-carrying beams was observed in the 1D case 31 , as well as for the two-dimensional configuration at the THz radiation 35,36 and near-infrared single photons 37 .…”
mentioning
confidence: 99%
“…This phenomenon is well-studied, both theoretically and experimentally, for plane waves 33 and theoretically investigated for the beams comprising phase singularities 20,34,35 . In the experiment, the Talbot effect of the OAM-carrying beams was observed in the 1D case 31 , as well as for the two-dimensional configuration at the THz radiation 35,36 and near-infrared single photons 37 . In the 1D case 31 , the experimental intensity patterns were in the form of a periodic set of stripes, while for two-dimensional configuration there is an array of beams with a topological charge.…”
mentioning
confidence: 99%